The reality of using the integrated education systems (Virtual School Platform) and the difficulties of using it from the point of view of Mecca teachers - Al-Rishi, Hanan Muhammad Hazaa (Journal of Educational and Psychological Sciences, 2020)
The study aimed to stop the reality of using the unified education system (the virtual school platform) and the obstacles to its use by teachers in the city of Mecca light of some variables. The study adopted the descriptive analytical approach, and the study community was the teachers and teachers of the schools of the city of Mecca, numbering (28477) teachers Female teacher, 379 male and female teachers were randomly chosen, representing the study sample, and the study used a questionnaire to collect data related to the reality of the use of the unified education system and the obstacles to its use, and the study concluded that the reality of the use of teachers and teachers in the city of Mecca for the unified education system came with a high degree and an arithmetic average (3.61) A percentage of (72.2%), and male and female teachers face obstacles in using the system at an average degree, with an average of (3.22) and a percentage of (64.5%). The results also indicated that there were no statistically significant differences between the responses of the study sample in using a system Standardized education is attributed to gender, years of experience, age, or educational qualification; The study came out with a set of recommendations, the most important of which were holding training workshops for male and female teachers to develop their capabilities and their continued use of the unified education system, and urged them to develop their use of the system through extension and educational meetings.
Keywords: Unified Education System; Virtual School; teachers of Mecca